Ectopic pregnancy in noncommunicating horn of unicornuate uterus: 3D‐ultrasound and primary laparoscopic management. Issue 5 (24th May 2021) - Dhanawat, Juhi; Pape, Julian; Stuhlmann‐Laeisz, Christiane; Maass, Nicolai; Freytag, Damaris; Gitas, Georgios; Alkatout, Ibrahim
Abstract: Unicornuate uterus with pregnancy in the noncommunicating rudimentary horn is extremely rare. Diagnosis requires awareness, high suspicion index, 3D ultrasound, and MRI. If missed, it can be catastrophic. Treatment varies across literature. We present a case where detection was done by 3D ultrasound and primary laparoscopic surgery done for treatment. Abstract : All pregnant women should be eyed with suspicion of a mullerian anomaly and ectopic pregnancy. Being aware is the key to avoid catastrophes. A good ultrasound, 2D with 3D confirms diagnosis. Laparoscopic intervention is a good treatment choice.